2010
DOI: 10.1002/dvdy.22265
|View full text |Cite
|
Sign up to set email alerts
|

How does the tubular embryonic heart work? Looking for the physical mechanism generating unidirectional blood flow in the valveless embryonic heart tube

Abstract: The heart is the first organ to function in vertebrate embryos. The human heart, for example, starts beating around the 21st embryonic day. During the initial phase of its pumping action, the embryonic heart is seen as a pulsating blood vessel that is built up by (1) an inner endothelial tube lacking valves, (2) a middle layer of extracellular matrix, and (3) an outer myocardial tube. Despite the absence of valves, this tubular heart generates unidirectional blood flow. This fact poses the question how it work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 58 publications
1
76
0
Order By: Relevance
“…These traveling mechanical waves were traditionally considered myocardial peristaltic waves (Xavier-Neto et al, 2007) and tubular embryonic heart was accepted to work like a technical roller peristaltic pump (Manner et al, 2010). Experiments on zebrafish embryos offer an alternative theory (Forouhar et al, 2006): (I) While peak flow velocity generated by a roller peristaltic pump corresponds to the speed of a compression wave, peak ventricular inflow velocity of an embryonic zebrafish heart recorded exceeds the speed of a traveling contraction wave.…”
Section: Foce Generation Of the Tubular Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…These traveling mechanical waves were traditionally considered myocardial peristaltic waves (Xavier-Neto et al, 2007) and tubular embryonic heart was accepted to work like a technical roller peristaltic pump (Manner et al, 2010). Experiments on zebrafish embryos offer an alternative theory (Forouhar et al, 2006): (I) While peak flow velocity generated by a roller peristaltic pump corresponds to the speed of a compression wave, peak ventricular inflow velocity of an embryonic zebrafish heart recorded exceeds the speed of a traveling contraction wave.…”
Section: Foce Generation Of the Tubular Heartmentioning
confidence: 99%
“…Several other studies support these findings. The tubular embryonic heart does not function as a technical roller peristaltic pump (Hu and Clark, 1989; Butcher et al, 2007), but may be considered a valveless “Liebau pump” (also known as suction or impedance pump) (Manner et al, 2010). Valveless pumping can be achieved experimentally by periodically compressing the asymmetric site of a fluid filled tube made up of stiff and soft elastic sections (Liebau, 1955, 1956; Ottesen, 2003; Hickerson et al, 2005).…”
Section: Foce Generation Of the Tubular Heartmentioning
confidence: 99%
“…Besides its function to activate the transcription of genes, WT1 is also involved in posttranscriptional processes (3). The expression of WT1 is essential during development of multiple organs, including kidneys, gonads, spleen, and the heart (4,5). In the developing heart, WT1 is strongly expressed in the outer layer, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the efficiency of the valveless pumping in the tubular heart is increased due to its unique anatomy and the range of working parameters. One of the major claims against the theory of valveless suction pumping of the heart was the presence of negative outflows at some frequencies (Männer et al, 2010). The present Table 1 for each case.…”
Section: Discussionmentioning
confidence: 99%